Curcumin, a Secondary Metabolite, Activates the Defense System by Regulating Water Status, PSII Photochemistry, and Antioxidant Capacity in Lactuca sativa Exposed to Lead and/or Arsenic Stresses - Ayşenur Tofan; Emirhan Gurkan; Busra Arikan‐Abdulveli; Melike Balci; Evren Yildiztugay; Ceyda Ozfidan‐Konakci (Food and Energy Security, 2025)
ABSTRACT Lead (Pb) and arsenic (As) pollution seriously affect the physiological and biochemical processes of plants, reduce agricultural productivity, and pose a serious threat to human health. Recently, there has been an increasing interest in studies aimed at mitigating these negative effects of heavy metals. Curcumin is an important secondary metabolite belonging to the polyphenol class that provides stress tolerance to plants through its metal‐chelating activity. Therefore, in our study, curcumin (Cur1; 50 μM and Cur2; 100 μM) was applied to lettuce (Lactuca sativa L.) under lead (Pb; 100 μM) and/or arsenic (As; 100 μM) stress. It was observed that the relative growth rate of the plant decreased by 12% at Pb stress and 27% under As stress. Pb and combined stress conditions (Pb + As) reduced the relative water content by 23%. Notably, significant increases in these parameters were observed following curcumin treatment. Furthermore, exogenous curcumin application effectively mitigated the detrimental effects induced by heavy‐metal stress. On gas exchange and photosynthetic parameters, Cur1 treatment resulted in more than a twofold increase in carbon assimilation rate under Pb and Pb + As conditions. Due to Pb + As exposure, H2O2 content increased by 25% and TBARS content increased by twofold. These elevations were attenuated by curcumin with enhanced antioxidant enzyme activity. Compared to the combined stress exposure, Pb + As + Cur1 and Pb + As + Cur2 treatments resulted in 40% and 24% increased SOD activity, respectively. Curcumin treatments contributed to the maintenance of redox balance in the cell by increasing the activity of the ascorbate–glutathione (AsA‐GSH) cycle. In conclusion, curcumin applications to lettuce under Pb and/or As stress contributed to the reduction of ROS accumulation by increasing the water uptake, photosynthesis efficiency, and antioxidant enzyme capacity. These findings suggest that phenolic compounds like curcumin could be a promising strategy in agricultural practices to enhance plant resistance to heavy‐metal stress, thereby improving productivity.